Istinto di morte e conoscenza, 40 anni dopo. Firenze, 30 aprile 2010. Università di Firenze, Polo delle scienze sociali - Vari, Autori (Il sogno della farfalla, 2011)
On the 30th April 2010 the new edition of M. Fagioli’s Death Instinct and Knowledge was presented at the lecture theatre of the Polo delle Scienze Sociali (Social Sciences Decentralized Structure) of the University of Florence. The economist Anna Pettini, the linguist Federico Masini and the psychiatrist Paolo Fiori Nastro all spoke highlighting the significant impact of Fagioli’s human birth theory on their particular fields. A debate followed extending the research even further into other fields such as epistemology, philosophy, social sciences and law.